2010
DOI: 10.1080/08964281003774919
|View full text |Cite
|
Sign up to set email alerts
|

Effort-Reward Imbalance for Learning is Associated with Fatigue in School Children

Abstract: We examined relationships among fatigue, sleep quality, and effort-reward imbalance for learning in school children. We developed an effort-reward for learning scale in school students and examined its reliability and validity. Self-administered surveys, including the effort reward for leaning scale and fatigue scale, were completed by 1,023 elementary school students (grades 4-6) and 1,361 junior high school students (grades 7-9) at the end of 2006. Effort-reward imbalance for learning was associated with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 45 publications
1
23
1
Order By: Relevance
“…Short-term, transient feelings of fatigue or energy are defined as "state" mood or "state" affect in psychological literature [1][2][3][4]; and are related to a number of adverse health and quality of life-related outcomes, including lost work productivity [5], school absences [6], and negative health consequences [7]. Many factors could affect fatigue or energy states.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term, transient feelings of fatigue or energy are defined as "state" mood or "state" affect in psychological literature [1][2][3][4]; and are related to a number of adverse health and quality of life-related outcomes, including lost work productivity [5], school absences [6], and negative health consequences [7]. Many factors could affect fatigue or energy states.…”
Section: Introductionmentioning
confidence: 99%
“…Feelings of low energy and fatigue contribute to automobile accidents [1], reduced school attendance [2], and poor academic performance in adolescents [3]. Prevalence of severe fatigue has ranged from 11% to 60% across studies of European and United States adolescents [4–7], while prevalence of prolonged fatigue has ranged from ~1% – ~7.5% among community samples of adolescents [8–10].…”
Section: Introductionmentioning
confidence: 99%
“…It was confirmed that K-SADS-PL-J scored well on Cohen's Îş (ADHD = 1.00, disruptive behavior disorder = 0.91, anxiety disorders = 0.76, tic disorders = 0.75) for inter-rater reliability by the simultaneous interview method and had concurrent validity for ADHD, disruptive behavior disorder, and anxiety disorders using various evaluation scales (Miyawaki et al, 2003). As additional instruments for diagnoses and ADHD symptom severity, we used the Japanese versions of the ADHD Rating Scale-IV (ADHD-RS-IV-J) (Yamazaki, 2003), the Barratt impulsiveness scale (BIS) (Someya et al, 2001), strengths and difficulties questionnaires (SDQ) (Iizuka et al, 2010), a scale of intrinsic versus extrinsic motivation toward learning (IEML) (Sakurai and Takano, 1985), the effort–reward imbalance for learning model questionnaire (LERI) (Fukuda et al, 2010) and the Chalder fatigue scale (CFS) (Tanaka et al, 2008). Exclusion criteria for participants with ADHD were premature birth (gestation ≤ 36 weeks) and diagnosis of any bipolar, psychotic, obsessive–compulsive, or tic disorder at any point in their lifetime.…”
Section: Methodsmentioning
confidence: 99%